META ANALYSIS: THE EFFECT OF AUGMENTED REALITY ON STUDENTS' GEOGRAPHY LEARNING OUTCOMES IN SCHOOLS - Lubis, Darwin Parlaungan; Anja Kusumawati, Eka Suci; Rahmadi, M Taufik; Sugiharto,; Permana, Sendi; Pratama, Alvin; Suciani, Ayu; Siahaan, Nurhalimah (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2025)
Geography learning outcomes reflect the success of the learning process, particularly in the cognitive domain. However, many students struggle to understand abstract geographical concepts that are ideally taught in natural settings. This study aims to analyze the impact of augmented reality (AR) as a learning medium on geography learning outcomes. Using a quantitative meta-analysis method, 14 ISSN-certified national journal articles were reviewed. The results show that AR significantly enhances geography learning outcomes, with an average effect size of 0.34, indicating a strong positive impact. he results show that AR significantly enhances geography learning outcomes, with an average effect size of 0.34. According to Cohen's criteria, this value is categorized as a large effect, signifying that AR has a substantial and meaningful impact on students’ understanding of abstract geographical concepts. This effect size also surpasses that typically reported for conventional learning media, highlighting the innovative advantage of AR in geography education. Keywords: Augmented Reality, Learning Outcomes, Meta-analysis